1986
DOI: 10.3171/jns.1986.65.1.0086
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure, cerebral blood flow, and cerebrospinal fluid formation during hyperammonemia in cat

Abstract: Intracranial pressure (ICP), cerebral blood flow (CBF), and the cerebrospinal fluid (CSF) formation rate were examined in anesthetized cats during ammonia intoxication. Hyperammonemia, evoked by intravenous infusion of ammonium acetate, caused a significant increase in ICP when the arterial blood ammonia level exceeded 400 mumol X liter-1. A progressive elevation of blood ammonia concentration was followed by a gradual rise in CBF, measured by the xenon-133 clearance technique. At an arterial blood ammonia lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
3
1
1
Order By: Relevance
“…In favor of this hypothesis, administration of the glutamine synthetase inhibitor, methionine sulfoximine, reduces ammonia-induced brain edema both in vitro 27 and in vivo. 28,29 However, in the present study, hypothermia-induced reductions in brain-water content in ALF rats were not accompanied by significant reductions of extracellular brain glutamine at time points associated with brain edema. These findings suggest that mild hypothermia' s major protective effect on brain edema in this model of ALF is not mediated via an effect on brain glutamine synthesis.…”
Section: Discussioncontrasting
confidence: 73%
“…In favor of this hypothesis, administration of the glutamine synthetase inhibitor, methionine sulfoximine, reduces ammonia-induced brain edema both in vitro 27 and in vivo. 28,29 However, in the present study, hypothermia-induced reductions in brain-water content in ALF rats were not accompanied by significant reductions of extracellular brain glutamine at time points associated with brain edema. These findings suggest that mild hypothermia' s major protective effect on brain edema in this model of ALF is not mediated via an effect on brain glutamine synthesis.…”
Section: Discussioncontrasting
confidence: 73%
“…21 Because astrocytes are rich in Gln synthetase, it has been suggested that ammonia-induced astrocyte Gln accumulation creates an osmotic gradient that causes a shift of water into the astrocytes, resulting in astrocyte swelling, cerebral edema, and increased intracranial pressure. 19,22 It was also demonstrated that the cerebral edema associated with hyperammonemia can be prevented by preventing Gln accumulation in the brain, suggesting that hyperammonemia is necessary but not sufficient to produce cerebral edema. 23 Supporting this hypothesis, the cerebrospinal Gln concentrations in patients with OTCD are extraordinarily high during hyperammonemic encephalopathy.…”
Section: Discussionmentioning
confidence: 96%
“…Because of the intimate relationship of the astrocyte processes with cerebral capillaries and venules, it is not surprising that alterations of cerebral blood flow are commonly found in experimental hyperammonemia. 18,19 We performed 1 HMRS in the normal-appearing posterior centrum semiovale in five of the six patients with OTCD. We could not completely exclude contamination of faint T2 prolongation and minimal CSF in Patient 1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pro-posed that ammonia-induced brain edema in ALF involves alterations in astrocytic in-tracellular osmolarity resulting from glutamine accumulation (Cordoba et al, 1996). This is supported by studies demonstrating the administration of the glutamine synthetase inhibition, methionine sulfoximine, reduces ammonia-induced brain edema both in vitro (Norenberg and Bender, 1994) and in vivo (Chodobski et al, 1986;Takahashi et al, 1991). However, recently hypothermia-induced reductions in brain water content in ALF rats were not accompanied by significant reductions of microdialysate (extracellular) brain glutamine (Rose et al, 2000) or brain glutamine (Chatauret et al, 2003) at time points associated with brain edema.…”
Section: The Pathophysiology Of Hypothermia-effect On the Brainmentioning
confidence: 95%